KAJIAN PERILAKU BELANJA KONSUMEN MENGGUNAKAN TEKNIK ASOSIASI DI SUPERMARKET (STUDI KASUS: TOSERBA X). [STUDY OF CONSUMER SHOPPING BEHAVIOR USING ASSOCIATION TECHNIQUES IN SUPERMARKET (CASE STUDY: TOSERBA X)] - Ronny Samsul Bahri; Laura Lahindah (Universitas Pelita Harapan, 2020)
The development of retail companies in Indonesia is quite rapid causing the need for the use of data as a basis for decision making. As one of the developing retail stores, the floor display pattern has not been well managed and has not been linked to the pattern of consumer spending. Market basket analysis is one of the data mining method techniques to determine the association of consumer spending patterns in a purchase transaction. This study aims to determine whether there is an association pattern in each term of consumer spending in five divisions of supermarket products (all divisions, food, non-food, household or GMS & fresh). The term is divided into three, namely, term I (1-10), term II (11-20) and term III (21-month end). The data is processed using software Rapidminer version 5. The data processing results show an association relationship in several terms, namely all divisions in term I have influence, term II has no influence, term III has influence. Food division in term I has an influence, term II has no influence, term III has an effect. The nonfood division in term I has no influence, term II has no influence, term III has no effect. The GMS division in term I has no influence, term II has no influence, term III has no effect. The fresh division in term I has influence, term II has influence, term III has no effect. By using the results of the analysis, floor display and promotion patterns can be adjusted according to the consumer's shopping patterns. Abstrak dalam Bahasa Indonesia.Perkembangan perusahaan ritel di Indonesia yang cukup pesat menyebabkan perlunya pemanfaatan data sebagai dasar dalam pengambilan keputusan. Sebagai salah satu toko ritel yang sedang berkembang, pola pemajangan floor diplay belum dikelola dengan baik dan belum dikaitkan dengan pola belanja konsumennya. Market basket analysis merupakan salah satu teknik metoda data mining untuk menentukan hubungan asosiasi pola belanja kosumen dalam suatu transaksi pembelian. Penelitian ini bertujuan untuk mengetahui apakah terdapat pola asosiasi pada setiap termin pembelanjaan konsumen pada lima divisi produk supermarket (seluruh divisi, food, nonfood, household atau GMS & fresh). Termin terbagi menjadi tiga yaitu, termin I (tanggal 1-10), termin II (tanggal 11-20) dan termin III (tanggal 21-akhir bulan). Data diolah dengan menggunakan Software Rapidminer versi 5. Hasil pengolahan data menunjukkan adanya hubungan asosiasi pada beberapa termin yaitu Seluruh divisi dalam termin I ada pengaruh, termin II tidak ada pengaruh, termin III ada pengaruh. Divisi food dalam termin I ada pengaruh, termin II tidak ada pengaruh, termin III ada pengaruh. Divisi nonfood dalam termin I tidak ada pengaruh, termin II tidak ada pengaruh, termin III tidak ada pengaruh. Divisi GMS dalam termin I ada pengaruh, termin II tidak ada pengaruh, termin III tidak ada pengaruh. Divisi fresh dalam termin I ada pengaruh, termin II ada pengaruh, termin III tidak ada pengaruh. Dengan menggunakan hasil analisis, pola pemajangan floor display dan promosi dapat diselaraskan sesuai dengan pola belanja konsumen tersebut.